Inflammation, endothelium, and coagulation in sepsis - Schouten, Marcel; Wiersinga, Willem Joost; Levi, Marcel; Poll, Tom (Journal of leukocyte biology, 2008)
Sepsis is a systemic response to infection, and symptoms are produced by host defense systems rather than by the invading pathogens. Amongst the most prominent features of sepsis, contributing significantly to its outcome, is activation of coagulation with concurrent down‐regulation of anticoagulant systems and fibrinolysis. Inflammation‐induced coagulation on its turn contributes to inflammation. Another important feature of sepsis, associated with key symptoms such as hypovolemia and hypotension, is endothelial dysfunction. Under normal conditions, the endothelium provides for an anticoagulant surface, a property that is lost in sepsis. In this review, data about the interplay between inflammation and coagulation in sepsis are summarized with a special focus on the influence of the endothelium on inflammation‐induced coagulation and vice versa. Possible procoagulant properties of the endothelium are described, such as expression of tissue factor (TF) and von Willebrand factor and interaction with platelets. Possible procoagulant roles of microparticles, circulating endothelial cells and endothelial apoptosis, are also discussed. Moreover, the important roles of the endothelium in down‐regulating the anticoagulants TF pathway inhibitor, antithrombin, and the protein C (PC) system and inhibition of fibrinolysis are discussed. The influence of coagulation on its turn on inflammation and the endothelium is described with a special focus on protease‐activated receptors (PARs). We conclude that the relationship between endothelium and coagulation in sepsis is tight and that further research is needed, for example, to better understand the role of activated PC signaling via PAR‐1, the role of the endothelial PC receptor herein, and the role of the glycocalyx.